2022
DOI: 10.3389/fphys.2022.887207
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Fecal Microbiome and Metabolomics Reveals a Novel Potential Biomarker for Predicting Tibial Dyschondroplasia in Chickens

Abstract: Tibial dyschondroplasia (TD) is a metabolic tibial-tarsal disorder occurring in fast-growing poultry, and its diagnosis is mainly based on an invasive method. Here, we profiled the fecal gut microbiome and metabolome of broilers with and without TD to identify potential non-invasive and non-stress biomarkers of TD. First, TD broilers with the most pronounced clinical signs during the experiment were screened and faecal samples were collected for integrated microbiome and metabolomics analysis. Moreover, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…AFB1 is a class of highly toxic mycotoxins, and the waste of feed ingredients and decreased animal performance caused by AFB1 contamination have brought heavy economic losses to the livestock industry [ 36 ]. As a flavonoid herbal medicine extract, TFRD has various bioactive effects, including immunomodulatory, anti-inflammatory, antioxidant, and anti-apoptotic effects [ 1 , 5 , 29 , 31 ]. In this present experiment, the main active ingredient of TFRD is Rutin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFB1 is a class of highly toxic mycotoxins, and the waste of feed ingredients and decreased animal performance caused by AFB1 contamination have brought heavy economic losses to the livestock industry [ 36 ]. As a flavonoid herbal medicine extract, TFRD has various bioactive effects, including immunomodulatory, anti-inflammatory, antioxidant, and anti-apoptotic effects [ 1 , 5 , 29 , 31 ]. In this present experiment, the main active ingredient of TFRD is Rutin .…”
Section: Discussionmentioning
confidence: 99%
“…Microbial genomic DNA was extracted from duodenal content samples using the FastDNA SPIN kit (#116540600) according to the kit’s protocol and then stored at −20 °C before further analysis (MP Biomedicals, Santa Ana, CA, USA). Raw data were analyzed using the QIIME2 platform, as previously described [ 31 ]. Additionally, α and β diversities were determined in QIIME2.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a close relationship between bone health and gut microbiota was also found in broilers. The abundance of microbiota in the small and large intestines of TD broilers was significantly different from that in healthy broilers examined using high-throughput sequencing [ 25 , 67 ]. Additionally, by analysing the intestinal microbial diversity of patients with osteoporosis and osteopenia, it was found that the bacterial composition and diversity of the two groups changed compared to that of the normal group [ 68 ].…”
Section: Gut Microbiota and Bone Metabolismmentioning
confidence: 99%
“…TD has attracted more attention to poor animal welfare and causing huge economic losses to the flourishing poultry industry. Several studies have shown that some factors, including vasculature dysfunction 1 , high blood glucose levels 9 and variations in the gut microbiota (GM) 10 , substantially affect TD occurrence in broilers. However, the causes and specific pathogenesis of TD in chickens are still unknown.…”
Section: Introductionmentioning
confidence: 99%